2009
DOI: 10.1007/s12105-009-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma in the Young: A Spectrum or a Distinct Group? Part 1

Abstract: While most head and neck squamous carcinoma (HNSCC) occurs in older people, an increasing number of young patients are being affected worldwide, with up to 5.5% \40. These are predominantly oral and oropharyngeal cancers. Some patients have heavy exposure to the usual risk factors, but an increasing number do not. Part of this trend appears to be due to rising numbers of HPV associated tonsil carcinoma, particularly in males (smokers and non-smokers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 16 publications
2
59
0
6
Order By: Relevance
“…Regarding the gender of the patients, previous studies have shown a decrease of male to female ratio in sex distribution of young patients (Toner & O'Regan, 2009) and Patel et al reported that SCC of the oral cavity, specifically oral tongue, is increasing among young white individuals and that the increasing trend was significantly greater in young white women compared with that of young white men (Patel et al, 2011); this change in the incidence can be due to increased trends of smoking and/ or drinking in women and the greater prevalence in men can be caused by their more exposure to occupational carcinogens, toxins and other risk factors like marijuana compared to women (Dahlstrom et al, 2008). In our study only 43/262 (16.4%) of the patients were females, possibly reflecting the existing difference in prevalence of smoking or drinking between Iranian men and women.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Regarding the gender of the patients, previous studies have shown a decrease of male to female ratio in sex distribution of young patients (Toner & O'Regan, 2009) and Patel et al reported that SCC of the oral cavity, specifically oral tongue, is increasing among young white individuals and that the increasing trend was significantly greater in young white women compared with that of young white men (Patel et al, 2011); this change in the incidence can be due to increased trends of smoking and/ or drinking in women and the greater prevalence in men can be caused by their more exposure to occupational carcinogens, toxins and other risk factors like marijuana compared to women (Dahlstrom et al, 2008). In our study only 43/262 (16.4%) of the patients were females, possibly reflecting the existing difference in prevalence of smoking or drinking between Iranian men and women.…”
Section: Discussionmentioning
confidence: 94%
“…In the study of Irish patients with HNSCC by O'Regan et al (2006), 17% of young adults and none of the patients younger than 30 years had ever smoked cigarettes. Absence of conventional risk factors such as alcohol consumption and smoking in these patients proposes the presence of other possible risk factors in developing HNSCC especially in young patients (O'Regan et al, 2006;Toner & O'Regan, 2009). The suggested risk factors include certain types of viral infections such as HPV, poor diet, immunosuppression, marijuana exposure, poor dental hygiene, gastrointestinal reflux and genetic predisposition Dahlstrom et al, 2008;Westra, 2009;Rutt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La langue est la localisation la plus fréquente et représente entre 25 et 40 % des cancers buccaux [2]. Alors que les cancers buccaux diminuent chez les sujets de plus de 50 ans, différentes études ont rapporté une augmentation de l'incidence (jusqu'à 6 %) des cancers de l'amygdale et de la langue et les sujets atteints ont moins de 40 ans [3][4][5][6][7]. Ce nouveau groupe de patients présenterait un profil clinique particulier et une association limitée aux facteurs de risque « classiques » comme le tabac et l'alcool, puisque la plupart des études n'ont trouvé aucune association entre la consommation alcoolo-tabagique et la survenue de ces cancers.…”
unclassified